Mechanical and Biological Properties of Nondecellularized Human Wharton's Jelly Matrix for Soft Tissue Graft Material: An In Vitro Study - Kuntjoro, Mefina; Hendrijantini, Nike; Prasetyo, Eric Priyo; Atikasari, Nurani; Danaswari, Made Shintya; Hong, Guang (European Journal of Dentistry, 2025)
This study aims to determine the mechanical properties of hWJM through ultimate tensile strength (UTS) and elastic modulus tests, degradation, and porosity tests. Additionally, it evaluates the biological properties of hWJM by assessing growth factor secretion (fibroblast growth factor-2 [FGF-2] and vascular endothelial growth factor-A [VEGF-A]).For the mechanical tests, two groups were analyzed: group 1 was tested in a wet condition and group 2 in a dry condition. Degradation tests were conducted using phosphate buffer saline (PBS), collagenase enzyme, and simulated body fluid (SBF). The porosity test was conducted using a scanning electron microscope (SEM). For the biological tests, two groups were analyzed: group 1 consisted of nondecellularized hWJM and group 2 of human umbilical cord mesenchymal stem cells. All the data were collected and analyzed statistically.The mean ± standard deviation of the UTS test for group 1 was 0.787 ± 0.356 MPa, while for group 2, it was 1.897 ± 0.582 MPa. The elastic modulus test results were 0.568 ± 0.206 MPa for group 1 and 6.354 ± 2.985 MPa for group 2. The result showed that PBS degradation was 22% on day 14 and 39% on day 28. The collagenase enzyme degraded 15% after 1 hour, 63% after 6 hours, and 74% after 24 hours. SBF degradation rates were 10.3% after 1 week, 10.5% after 2 weeks, 12.5% after 4 weeks, and 13.9% after 8 weeks. The porosity test results showed an average pore size of 66.95 μm. For the biological tests, no significant differences in FGF-2 and VEGF secretion were observed between groups, with the highest secretion in group 1 occurring on day 7.Nondecellularized hWJM has been shown to meet the physical, mechanical, and biological criteria for soft tissue graft in dentistry.
Keywords: tissue engineering; regeneration; allograft; freeze drying; medicine